Additive Manufacturing of Dense Ceramic Parts via Direct Ink Writing of Aqueous Alumina Suspensions. Issue 5 (14th June 2016) - Rueschhoff, Lisa; Costakis, William; Michie, Matthew; Youngblood, Jeffrey; Trice, Rodney
Abstract : Additive manufacturing of near‐net‐shaped dense ceramic components has been established via room‐temperature direct writing of highly loaded aqueous alumina suspensions in a layer‐by‐layer fashion. The effect of alumina solid loading on rheology, specimen uniformity, density, microstructure, and mechanical properties was studied. All suspensions contained a polymer binder (~5 vol.%), dispersant, and 51–58 vol.% alumina powder. Rheological measurements indicated all suspensions to be yield‐pseuodoplastic, and both yield stress and viscosity were found to increase with increasing alumina solid loading. Shear rates ranging from 19.5 to 24.2/s, corresponding to viscosities of 9.8 to 17.2 Pa·s, for the 53–56 vol.% alumina suspensions were found to produce the best results for the 1.25‐mm tip employed during writing. All parts were sintered to >98% of true density, with grain sizes ranging from 3.2 to 3.7 μm. The average flexure strength, which ranged from 134 to 157 MPa, was not influenced by the alumina solid loading.